Habitat mapping and conservation threats to river dolphin in Karnali River of Nepal - Malla, R (Banko Janakari, 2009)
This study was carried out in the Karnali River of Nepal with the aims of preparing habitat map of dolphins in the Karnali River and assessing conservation threats to dolphin at the local level. The habitat map of the dolphin was prepared on the basis of study and local sightings. Altogether 100 households were surveyed around the Karnali River living within 3 km from the river distance. Questionnaire survey, group discussion, field observation and key-informants interviews were conducted to assess conservation threats to dolphin at the local level. Statistical tools like Pie chart and bar diagram were used to analyze the data. Use of poison in the river, commercial and domestic consumption of fishes, and high dependency of people in the river are emerging as the threats to dolphin conservation. Similarly, the increasing trend of using chemical fertilizer in the agriculture land is also adding up to long term negative impacts on dolphin population. Regular habitat monitoring of the dolphins should be done in major areas to acquire timely information on status and distribution of dolphins for dolphin conservation. Also, local people should be provided with alternate incentives by actively mobilizing them in dolphin conservation work Key words: Dolphins, habitat mapping, conservation threats, Karnali river doi: 10.3126/banko.v19i3.2208 Banko Janakari, Special Issue February 2009, 24-29